Poesia infantil no Rio Grande do Sul - Domingues, Cristiane Lumertz Klein (2011)
The paper entitled Poetry for children in Rio Grande do Sul (1882-2011) trends and thematic anthology intends to seek for authors who have dedicated to writing for children, in order to collect poems addressed to children written in our state, to organize a catalog completeness of this literature. Therefore, this work begins with the study of the origins of childhood, by relating the rise of literature for children with the history of narrative and poetry for children in Brazil and Rio Grande do Sul. Later on, the concept of poetry and the specificity of children's poetry is studied, as well as the corpus of themes and trends that moves the young reader. From the theoretical reference, the selection and analysis of the poems listed in the corpus of works is done. Then, as a result of the research, it is presented a anthology of poems, which is enclosed. This selection is based on theoretical studies and resulted in a total of 48 poems, divided into six thematic trends. Also enclosed, there is a list of pieces of children s poetry written in Rio Grande do Sul, organized by date of publication, author, place of publication and publisher.